Factores de riesgos financieros en empresas de logística (transporte ferroviario): zona metropolitana de Guadalajara, Jalisco (2021)
Mexico, one of the countries with greatest natural wealth, makes a very attractive commercial partner for the rest of the countries, either for promotion or production processes. In this context, according to the interests of this article, rail transport is mainly used to move goods for import or export. Year by year, in the metropolitan area of Guadalajara, there is an increase in the construction sector that now “represents 11% of the gross domestic product in Jalisco” (Mexican Chamber of the Construction Industry, 2021) and for this, the distribution of various products and raw materials is needed, including heavy machinery and raw materials such as stone (marble), which is difficult to move because of its volume and requires rail transport to be distributed. This research aims to identify through documentary analysis the financial risk factors that affect the distribution of stone (marble) and heavy machinery via rail transport, in companies located in the metropolitan area of Guadalajara, Jalisco.